2015
DOI: 10.3389/fpls.2015.00826
|View full text |Cite
|
Sign up to set email alerts
|

Integrative “omic” analysis reveals distinctive cold responses in leaves and roots of strawberry, Fragaria × ananassa ‘Korona’

Abstract: To assess underlying metabolic processes and regulatory mechanisms during cold exposure of strawberry, integrative “omic” approaches were applied to Fragaria × ananassa Duch. ‘Korona.’ Both root and leaf tissues were examined for responses to the cold acclimation processes. Levels of metabolites, proteins, and transcripts in tissues from plants grown at 18°C were compared to those following 1–10 days of cold (2°C) exposure. When leaves and roots were subjected to GC/TOF-MS-based metabolite profiling, about 160… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 83 publications
2
19
1
Order By: Relevance
“…4D ). These data suggest that survival of the pith tissue might be linked to high raffinose concentrations and are in line with previous reports, that showed that raffinose levels were elevated upon cold and freezing temperatures (Koehler et al, 2015; Yue et al, 2015). Such conditions induce the formation of reactive oxygen species (Gechev et al, 2006), which, when accumulating to high levels, can be harmful to the plant, as they can damage membranes (lipid peroxidation), proteins, RNA and DNA molecules (Choudhury et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…4D ). These data suggest that survival of the pith tissue might be linked to high raffinose concentrations and are in line with previous reports, that showed that raffinose levels were elevated upon cold and freezing temperatures (Koehler et al, 2015; Yue et al, 2015). Such conditions induce the formation of reactive oxygen species (Gechev et al, 2006), which, when accumulating to high levels, can be harmful to the plant, as they can damage membranes (lipid peroxidation), proteins, RNA and DNA molecules (Choudhury et al, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Dihydroflavonols are utilized in the biosynthesis of not only flavonols but also leucoanthocyanidins, which are utilized for the biosynthesis of anthocyanins and flavan-3-ols. The anthocyanin content observed in our study was lower than the content previously reported under cold treatment in leaves and fruits (Koehler et al, 2015;Tanou et al, 2017). The reduction of anthocyanins to flavan-3ols by anthocyanin reductases (ANRs) has previously been reported to contribute a major share of the flavan-3-ols in tobacco (Luo et al, 2016), cotton (Zhu et al, 2015), white clover (Abeynayake et al, 2012), grape (Bogs et al, 2007), and strawberry (Fischer et al, 2014).…”
Section: Variation In the Content Of Phenolic Classes In Response To Varied Nitrogen Supplycontrasting
confidence: 85%
“…treatments (Supplementary Figure 1). These metabolites are known for their role as osmoprotectants, scavengers of ROS, and signaling molecules and are reported to be upregulated under cold, heat, and drought stress (Nishizawa et al, 2008;Koehler et al, 2015). Organic acids derived from the anaplerotic TCA cycle act as transient carbon substrates for amino acid synthesis and as regulators of redox and energy levels (Igamberdiev and Eprintsev, 2016).…”
Section: Variation In the Content Of Primary Metabolites In Response To The Nitrogen Supplymentioning
confidence: 99%
“…To study the metabolic processes and regulatory mechanisms during cold exposure of strawberry, metabolite profiling approaches were applied to both root and leaf tissues (Koehler et al 2015; Rohloff et al 2012). About 160 substances comprising primary and secondary metabolites were quantitatively analysed.…”
Section: Biological Questionsmentioning
confidence: 99%